An integrated solution using bench spreadsheets to monitor Quality control indicators and performance in medicine laboratories - Miranda, Armandina (2023)
Laboratory Quality Control (LQC) in medical laboratories is a tool to monitor the procedures of pre analytical, intra analytical and post analytical phases. The data statistic analyze allow the quantification of the random errors using the variation coefficients (CV%) obtained by Internal Quality Control (IQC) and the systematic errors (bias%), from the results of External Quality Control (EQC). These results are combined to calculate the Total Error (TE) and Measurement of Uncertainty (MAU), that allows the knowledge of the precision and accuracy and follow the performance of laboratory by comparison with the quality specifications. The main objective is to present a tool as a bench spreadsheet developed in National Institute of Health Doctor Ricardo Jorge (INSA), aiming to help the national and portuguese speaking countries laboratories, to calculate the main indicators of the LQC: TE, Sigma level and MU using IQC and EQC results, in a simplified way.